One-Year Results of Photodynamic Therapy Combined with Intravitreal Ranibizumab for Exudative Age-Related Macular Degeneration - Tomoko Nakamura; Akio Miyakoshi; Kazuya Fujita; Tatsuya Yunoki; Keiichi Mitarai; Shuichiro Yanagisawa; Chiharu Fuchizawa; Atsushi Hayashi (Journal of Ophthalmology)
Purpose. To evaluate the effects of photodynamic therapy (PDT) combined with intravitreal injection of ranibizumab (IVR) for exudative age-related macular degeneration (AMD). Methods. Retrospective case series. Thirty eight eyes of 38 patients with exudative AMD underwent combined therapy consisting first of IVR, followed by PDT within a week and the second IVR at 1 month. All patients were followed up for more than 12 months. The best corrected visual acuity (BCVA) and central macular thickness (CMT) were examined. Results. The mean number of IVR and PDT sessions were 2.9±1.3 and 1.1±0.3, respectively. The mean BCVA and CMT were significantly improved to 0.38 logMAR units (𝑃<0.01) and 240 μm (𝑃<0.01) at 12 months, respectively. Thirty-six of 38 eyes (94.8%) improved or maintained BCVA at 12 months. Conclusion. PDT combined with IVR for exudative AMD was effective at improving visual acuity and CMT with a low recurrence rate for 12 months.